COMPLEX ESTIMATION OF WORKING CONDITIONS IN THE SHOPS OF NONFERROUS CASTINGS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия)
The results of complex estimation of the working conditions of workers in nonferrous foundries, which are received on the basis of investigations of working places space, are given.